Application of decoupling networks in deadbeat controller for high-frequency link inverter - Salam, Zainal; Soon, Toh Leong; Ramli, Mohd. Zulkifli (The Institution of Engineers, Malaysia, 2006)
Deadbeat is a control method that results in very fast dynamic response. However its application in power electronics converters is somewhat hindered because it is very sensitive towards parameter variations. In an attempt to improve this shortcoming, a modified Deadbeat controller with additional disturbance decoupling networks is introduced. The proposed controller consists of inner current loop, outer voltage loop and a feedforward controller. This scheme is applied to a high-frequency link inverter. A 1kVA prototype inverter is constructed and the performances of the proposed controller are experimentally verified, along with MATLAB-Simulink simulation. The results show that the proposed controller with decoupling networks has very fast dynamic response, and good steady-state response even under severe nonlinear loads.